If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -4) + 1 = 11 Reorder the terms: 2(-4 + 3x) + 1 = 11 (-4 * 2 + 3x * 2) + 1 = 11 (-8 + 6x) + 1 = 11 Reorder the terms: -8 + 1 + 6x = 11 Combine like terms: -8 + 1 = -7 -7 + 6x = 11 Solving -7 + 6x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 6x = 11 + 7 Combine like terms: -7 + 7 = 0 0 + 6x = 11 + 7 6x = 11 + 7 Combine like terms: 11 + 7 = 18 6x = 18 Divide each side by '6'. x = 3 Simplifying x = 3
| -28=-y^4-12 | | (4x+14)=90 | | 2/3s=6 | | 92.80/x=100 | | 8a+4b=64 | | 6n^5/5n^3 | | 10d=61-6 | | 2ln(7x)+3=12 | | 4-x^5=-16 | | 0.2(2x+1)-0.66(X-5)=5 | | ln15/100=lne^-.02x | | Y=cox+h | | -b^3+50=100 | | -3/5x-30 | | 3t+3=6t+3 | | [6x-3]=9 | | -5x+y=-8 | | -3z+30=3(5z-2) | | 10b^2-27+18=0 | | -3+30=3(5z-2) | | (x+-5)+-2=-10 | | 8y-6=5+12 | | 3a-2a^2= | | 6a-24b+12= | | -4(2p-4)=2(p+3) | | K/(-3)=-9 | | 7x(x+8)=231 | | b^2+5b=88 | | 2n+8=n-5 | | X+1.3(2)=x(3) | | -(4x+6)+3(x+8)=1-2x+2 | | 2(5x+1)=82 |